Dry-masonry Brick House System as an "Adaptable Building" Model for Asian Markets - Khamidi, Mohd. Faris (2005)
Since 1950, the world population has more than doubled where most of this growth has taken place in developing world. In the next two decades around 98% of world population growth will occur in developing countries and it is estimated that by 2007 half of this mushrooming population will live in urban areas. In Asia, though it covers only 30.2% of total world landmass. the total share of world population is the highest at 60.7% (censlIs 2002). These demographic dynamics (population growth, urbanisation etc) translate into increased demand for buildings and infrastructure in particular demand for shelter especially in the less developed countries. The developing world's share of world construction was only 10% in 1965. increased by almost threefold to 29% in 1988 and still growing. Studies conducted by utilizing data from 'Database of World Housing Stock & Construction' based on the Housing Settlements Database Version 4 (HSDB4) prepared by United Nations Human Settlements Programme (UN-HABITAT) shows that brick (masonry) remains as the main material in production and building stocks among Asian countries. It is necessary to note that there are many factors which prevent "adaptable buildings" to be realized and one of the main reasons is that due to the nature of the currently used construction method; various materials used in the construction industry are bonded and mixed to each other. Therefore there is an urgent need to change the currently used masonry construction method to keep abreast with latest sustainable building technology. Adapting a system that specifically design for the need to assembly and disassembly and also highly promotes "green cycle" that encompasses "reduce-reuse-recycle" is a remedy that may well solve the problems that have been plaguing the construction industry for years. Since October, 1997, a group of researchers led by Prof. Yasunori Matsufuji of Kyushu University has embarked a R&TD in what is called Dry-masonryl Brick House System (DBHS) that utilized a construction method called "Steel Reinforced Brick Construction based on Distributed Unbonded Prestress Theory" (SRB-DUP) as a tactic to carry out a sustainable strategy to be realized as "adaptable building" model. This paper discusses some case studies on how countries in Asian region namely Malaysia, Indonesia, China, India, Iran and Afghanistan can adapt DBI-IS as an "adaptable building" model that may well conform to the overall Sustainable Development Plan of these particular countries.